Pengaruh PPKM Terhadap Peningkatan Peran Guru pada Pembelajaran di Masa Pandemi Covid-19 - Suprijati Suprijati; Victor Novianto (UM Purwokerto Press, 2022)
Pandemic During the Covid-19 pandemic that is currently engulfing the world, including Indonesia, there have been various social movements aimed at tackling the outbreak. One of the social movements as a result of policies from the government in the context of dealing with Covid-19 is the implementation of PPKM which is always extended to an unpredictable time limit before Covid-19 disappears. PPKM has an impact on the implementation of learning in Indonesia. The purpose of writing this article is to find out how PPKM influences the increase in the role of teachers in learning in the Covid-19 pandemic era. In this study, the author uses qualitative methods through literature studies and documentation studies related to the influence of the PPKM social movement on increasing the role of teachers in the Covid-19 pandemic era from various relevant sources. The results of the discussion show the influence of PPKM on increasing the role of teachers in learning in the era of the covid-19 pandemic.